Advertising and Marketing Strategies: What crafters of new Kenya ought to learn - GM, MURIUKI ROBERT (IJRDO - Journal of Business Management, 2015)
Advertisers and marketers in new Kenya have vast opportunities to be exploited. Since the promulgation of the new constitution in 2010, devolution to the counties has extended frontiers in advertising and marketing. In the devolved system of government of Kenya today, a lot of financial and human resources have been directed to the counties where a lot of business can be made. This paper will look at advertising and marketing strategies the crafters of new Kenya ought to learn so as to maximize on their returns on investment. The paper will explore the changes that have occurred to marketing over time and those principles and practices that have endured. There are threats to traditional advertising that need to be embraced. It is important for the crafters on new Kenya to be alive to the fact that even with all the advantages of advertising, its ubiquitous nature has led to advertising–weary consumers who seize every available opportunity to avoid it. The crafters will also need to learn the new technologies that have impacted the way advertisement is done separate from traditional advertising. This paper will look at the new advertising platforms and new techniques that advertisers need to embrace. The paper also makes recommendations on what the crafters of new Kenya need to learn to mitigate the threats that engulf traditional advertising and marketing.